2019
DOI: 10.4142/jvs.2019.20.e29
|View full text |Cite
|
Sign up to set email alerts
|

Needleless intradermal vaccination for foot-and-mouth disease induced granuloma-free effective protection in pigs

Abstract: Vaccination is one of the most effective ways of controlling and preventing foot-and-mouth disease (FMD) outbreaks. The effective prevention of this disease requires the use of high-quality vaccines to meet the criteria that enable customers to use them simply. The administration of FMD vaccines containing oil-based adjuvants in pigs can induce the formation of granuloma in the muscle of the vaccinated, which makes these vaccines a less preferable option. Therefore, it is important to establish an FMD vaccine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Due to these advantageous features, several studies have investigated ID vaccines [8][9][10]. A previous study on a needle-free delivery system reported that FMD vaccination through the ID route using the same antigen as that used for IM vaccination effectively protected swine from FMDV [20].…”
Section: Discussionmentioning
confidence: 99%
“…Due to these advantageous features, several studies have investigated ID vaccines [8][9][10]. A previous study on a needle-free delivery system reported that FMD vaccination through the ID route using the same antigen as that used for IM vaccination effectively protected swine from FMDV [20].…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ-secreting cells reached maximum levels and upregulation of IFN-γ gene expression in PBMC was also detected in ID group pigs after administration of the booster dose by Aujeszky’s vaccine [ 29 ]. Another study that compared IM foot-and-mouth disease (FMD) vaccination with ID FMD vaccination suggested that the latter protects animals when their serum neutralization antibody titers are low [ 30 ]. Data suggests that this effect is partly associated with humoral immunity because ID vaccination is a major contributor to cell-mediated immune responses that induce mobilization of inflammatory dendritic cells [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Massive outbreaks of FMD in the Republic of Korea from 2010 to 2011 led to the implementation of various policies to break this economic cycle; specifically, the Republic of Korea has adopted policies of intramuscularly (IM) vaccinating all susceptible livestock with an inactivated FMD vaccine [ 5 , 6 ]. The adjuvants included in the vaccine regulate the immune response to the vaccine through inducing proinflammatory cytokine production and regulating the T-helper 1 (Th1)/T-helper 2 (Th2) balance, but the immune activation mediated by these adjuvants may lead to various local or systemic reactions, including strong immune response, potentially causing adverse effects [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The adjuvants included in the vaccine regulate the immune response to the vaccine through inducing proinflammatory cytokine production and regulating the T-helper 1 (Th1)/T-helper 2 (Th2) balance, but the immune activation mediated by these adjuvants may lead to various local or systemic reactions, including strong immune response, potentially causing adverse effects [ 7 ]. Therefore, excessive immune responses induced by preventive vaccines may lead to undesirable muscle and soft tissue changes in livestock that reduce meat quality, including granuloma, sterile abscess, residual vaccine, and nodular lesions in the muscle layer [ 6 , 8 ]. Undesirable vaccination-induced muscle and soft tissue changes persist for a long time and are observed even in slaughterhouses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation